JAK/STAT Signaling: Molecular Targets, Therapeutic Opportunities, and Limitations of Targeted Inhibitions in Solid Malignancies - Rah, Bilal; Rather, Rafiq A; Bhat, Gh Rasool; Baba, Abdul Basit; Mushtaq, Ifra; Farooq, Muzamil; Yousuf, Tahira; Dar, Sadaf B; Parveen, Sabra; Hassan, Rukhsana; Mohammad, Fozia; Qassim, Iqbal; et al. (Frontiers in Pharmacology, 2022)
Being implicated in the fundamental junctures of a plethora of signaling cascades, the JAK/STAT signaling pathway impacts an array of cellular processes such as cell proliferation, invasion, survival, apoptosis, inflammation, immunity, and hematopoiesis that are mandatory for tissue homeostasis and development in mammals. The majority of these cellular responses are initiated by cytokines, growth factors and hormones, and are mediated through JAK/STAT signaling. Mechanistically, JAK/STAT signaling is operated by a variety of ligands (cytokines, growth factors, hormones) and their respective cognate receptors. However, the underlying mechanism of how JAK/STAT mediates the development of solid tumors needs extensive research. STATs typically have a dual role when explored in the context of cancer. Although several STATs which encompass STAT1, STAT2, STAT3, STAT4, STAT5A, STAT5B, and STAT6 as a whole, participate in tumorigenesis, however, a few members which include STAT3 and STAT5 are linked to tumor initiation and progression, other STAT members which include STAT1 and STAT2 are pivotal for antitumor defense and maintenance of an effective and long-term immune response through evolutionarily conserved programs. Understanding the function of STAT specificity, redundancy, and connectedness in cancer is critical to improving the therapeutic outcome. A better understanding of the functionally redundant roles of JAKs and STATs may provide a rationale for improving existing cancer therapies and identifying novel targets for therapeutic intervention in solid tumors. The effects of JAK/STAT signaling and the persistent activation of STATs in tumor cell survival; proliferation and invasion have made the JAK/STAT pathway an ideal target for drug development and cancer therapy.